Effectiveness of several insecticides on red palm weevil, rhynchophorus ferrugineus on coconut palm - Azlina Zakaria; Meor Badli Shah Ahmad Rafie; Mohamad Haris Hussain; Johari Jalinas; Idris Ab Ghani (Penerbit Universiti Kebangsaan Malaysia, 2024)
Although report on Rhynchophorus ferrugineus (RPW) attacking and damaging the oil palm is virtually absent, the potential of host shift from coconut to oil palm is awaiting as it closely related species the R. vulneratus and R. schach have been reported to attack oil palm in Malaysia, Indonesia and India. Currently, there has been no effective control method of RPW identified, other than destroying the breeding sites of the RPW. Thus, this study was conducted to evaluate the efficacy of selected chemical insecticides in controlling RPW within the coconut palm trunk. The study site was selected based on RPW infestation report by Department of Agriculture Malaysia (2019). All coconut palms in the area were confirmed on the RPW presence by using acoustic detection method and visual symptoms inspection. Three different chemicals were tested, namely acephate (organophosphate), cypermethrin (pyrethroid) and carbosulfan (carbamate). 30 g of acephate was delivered via trunk injection method, while cypermethrin were sprayed with 500 ml solution per palm, and 60 g of carbosulfan was placed on the crown of each palm. The effectiveness of treatments was measured by the presence or absence of RPW in the palm trunk via acoustic detection method, at weekly interval until 7 weeks after treatment. At one week after treatment, reduction of RPW presence was 87.5% when treated with carbosulfan, followed by cypermethrin (57.14%) and acephate (53.85%). No absence of RPW in control treatment. As a conclusion, the most effective chemical pesticide in controlling RPW is carbosulfan and can be considered in the integrated pest management of RPW.